Empirical correlation of volumetric mass transfer coefficient for a rectangular internal-loop airlift bioreactor. Issue 4 (23rd May 2008) - Liu, Sean X.; Hermanowicz, Slawomir W.
Abstract : An empirical correlation of volumetric mass transfer coefficient was developed for a pilot-scale internal-loop rectangular airlift bioreactor that was designed for biotechnology. The empirical correlation combines classic turbulence theory, Kolmogorov's isotropic turbulence theory with Higbie's penetration theory. The simulation results based on the correlation suggested that the loading of polyethylene granules (for microbial colony support) in the bioreactor had little effect on the mass transfer coefficient of oxygen gas in the reactor, however, the gas superficial velocity was shown to affect the mass transfer coefficient substantially. These simulation results are comparable to the experimental results from a similar, albeit smaller in volume, three-phase internal-loop rectangular reactor in the literature.